(untitled) (American Journal of Islam and Society, 1992)
Efforts to foretell the future of the American Jewish community date far back to the nineteenth century, and for the most part the prophecies have been exceedingly gloomy. Former president John Adams predicted in a letter to Modecai Noah in 1819 that Jews might "possibly in time become liberal Unitatian Christians.” A young American Jewish student named William Rosenblatt, writing in 1872, declared that the grandchildren of Jewish immigrants to America would almost surely intermarry and abandon the rite of circumcision. Within fifty years “at the latest,” he predicted, Jews would be “undistinguishable from the mass of humanity which surrounds them.“ Just under a century later, in 1964, Look magazine devoted a whole issue to the “Vanishing American Jew,” at the time a much-discussed subject. More recently, in 1984, Rabbi Reuven Bulka, in a book entitled The Orthodox- Reform Rift and the Future of the Jewish People, warned that “we are heading towards a disaster of massive proportions which the North American Jewish community simply cannot afford.” So far, thank God, all of these predictions have proven wrong. The Jewish people lives on. Some might consider this a timely reminder that (as someone once said) “prediction is very difficult, especially about the future.“ Othem may view our continuing survival as nothing less than providential: evidence that God, in a display of His divine mercy, is watching over us. A third view, my own, is that precisely because Jews are so worried about survival, we listen attentively to prophets of doom and respond to them ...